Relation among the knee, sagittal spinal alignment, and the spinal range of motion: Investigation in local medical check-ups using the SpinalMouse - Shinya Yanagisawa; Naoki Sato; Masaki Shimizu; Kenichi Saito; Atsushi Yamamoto; Kenji Takagishi (Elsevier, 2015)
Background: This study was designed as an investigation in a local population to assess the relation between the knee joint and spinal alignment in a population-based study using the SpinalMouse. Methods: Medical check-ups were conducted for residents of a mountain village in Japan. The study population included 107 men and 157 women (528 knees) with a mean age of 71.1 ± 6.8 years (range, 60-87 years). A questionnaire dealing with any current symptoms involving the knees was administered, and physical examinations dealing with the range of motion (ROM) of knee were conducted. The SpinalMouse was used to measure sagittal spinal alignment and spinal ROM. The parameters considered were thoracic kyphosis angle, lumbar lordosis angle (LLA), sacral inclination angle (SIA), and trunk angle of inclination (INC). The patients were divided into a group with knee flexion contracture (FC group) and a group without knee FC (non-FC group) to conduct a comparative study of both groups. Results: With regard to static spinal alignment, LLA and SIA decreased significantly in the FC group (p < 0.05). With regard to spinal ROM, LLA and INC decreased significantly in the FC group (p < 0.05). Conclusion: Results suggested that the knee and the spine affect each other and that the spinal ROM is also involved. The current study may explain the development of knee-spine syndrome.